Papa pajchay, First contribution of potatoes - Vivanco Flores, Carlos A. (1971)
The papa pajchay or first hilling of the potatoes is done collectively or mink'a. In the district of Ocobamba it has not lost any of its originality. The person who has the work carried out on his farm selects a captain in advance, a position that generally falls to one of his compadres or other spiritual relatives. The captain is in charge of providing workers without prejudice to the fact that the owner also gets the peonada. The captain has the right to carry a flag adorned with countless bells, a sign of joy and also of purity, since agricultural work must be carried out with a calm soul. At work time, the captain heads the group of workers who work in organized teams.